BRAF inhibitors: resistance and the promise of combination treatments for melanoma - Griffin, Merope (Oncotarget, 2017)
Identification of mutations in the gene encoding the serine/threonine-protein kinase, BRAF, and constitutive activation of the mitogen-activated protein kinase (MAPK) pathway in around 50% of malignant melanomas have led to the development and regulatory approval of targeted pathway inhibitor drugs. A proportion of patients are intrinsically resistant to BRAF inhibitors, and most patients who initially respond, acquire resistance within months. In this review, we discuss pathway inhibitors and their mechanisms of resistance, and we focus on numerous efforts to improve clinical benefits through combining agents with disparate modes of action, including combinations with checkpoint inhibitor antibodies. We discuss the merits of combination strategies based on enhancing immune responses or overcoming tumor-associated immune escape mechanisms. Emerging insights into mechanisms of action, resistance pathways and their impact on host-tumor relationships will inform the design of optimal combinations therapies to improve outcomes for patients who currently do not benefit from recent treatment breakthroughs.